Pengaruh Amelioran Terak Baja dan Bokashi Sekam Padi terhadap Sifat Kimia, Fisika, dan Biologi Tanah - Priestiani, Priestiani; Muharani, Laily; Khasanah, Nur; Tumatul Aini, Dewi (Jurnal Inovasi Teknologi Terapan, 2025)
Andisol contains ingredients amorphous and non-crystalline clay that causes Andisol have high P-retention. Steel slag and bokashi of rice husk are expected not only to decrease P-retention but also to improve the chemical, physical and biological properties. This experiment was aimed to the interaction, relationship and combination steel slag with bokashi of rice husk to the chemical, physical and biological properties in Andisol. This study used a randomized block design factorial with two factors. The first factor was steel slag and the second factor was rice husk bokashi each consists of 4 levels is 0%, 2,5%, 5,0% and 7,5% ), so total of treatment were 4 x 4 = 16 combinations of treatments and 48 experimental plots. The results of this research showed that the interaction between steel slag with bokashi rice husks to decreased in soil bulk density, but there was no interaction effect on the P-available and total bacterial population. Provision of steel slag effect on P-available, but did not affect the total bacterial population. Bokashi Award rice husk did not affect the P-available and total bacterial population. There was the best treatment combination between steel slag 2.5% to 2.5% bokashi of rice husks decrease soil bulk density of 0.81 g cm-3 to 0.62 g cm-3.